Mini percutaneous nephrolithotomy. How good it is - a single centre experience - Qadri, Syed Javid F.; Ahmed, Mufti Mahmood; Khanday, Zafar S.; Leharwaal, Asim (International Surgery Journal, 2020)
Background: Percutaneous nephrolithotomy (PCNL) is one of the 1st line treatment options for managing renal stones. Miniaturization of this technique has been developed to decrease the morbidity of this technique without compromising the results. Mini PCNL (mPCNL) involves the use of small calibre sheath and nephroscope to tackle renal stones of small to moderate size. The aim of this study is to present the efficacy and technical advantages of mPCNL in managing renal stones. Methods: This was a retrospective single centre study of mPCNL in managing renal stones. Results: From July 2015 to July 2020 192 mPCNL procedures were done at our centre in 175 patients. The median number of stones was 1(1-3) and the average size of calculus was 18.5 mm (6-35) mm. Mean operative time in our study was 46 (35-92) minutes. Fever developed in 15 (7.8%) patients which was managed by parenteral antibiotics, none of our patients required ICU admission. Haemothorax developed in 2 (1%) patients and both of them were managed by tube thoracostomy. We achieved complete clearance in 183 (95.3%) cases. In 9 (4.7%) patients residual calculi were manged by flexible ureteroscopy at 1 month. Conclusions: mPCNL is an effective procedure for management of patients with renal stones with the advantages of less blood loss, short hospital stay and excellent stone clearance rate.